2022
DOI: 10.3171/2021.9.jns211738
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of postoperative seizure outcome in supratentorial meningioma

Abstract: OBJECTIVE Meningiomas are the most common primary intracranial tumor. Seizures are common sequelae of meningioma development. Meningioma patients with seizures can be effectively treated with resection, with reports of seizure freedom of 60%–90%. Still, many patients manifest persistent epilepsy. Determining factors associated with worsened seizure outcomes remains critical in improving the quality of life for these patients. The authors sought to identify clinical, radiological, and histological factors assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 39 publications
0
12
2
Order By: Relevance
“…Unlike a recent study [ 7 ], we did not find an association between infarctions and risk of postoperative epilepsy. However, we did not account for preoperative seizures in the analyses and with longer follow-ups frequencies of seizures would be expected to increase.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Unlike a recent study [ 7 ], we did not find an association between infarctions and risk of postoperative epilepsy. However, we did not account for preoperative seizures in the analyses and with longer follow-ups frequencies of seizures would be expected to increase.…”
Section: Discussioncontrasting
confidence: 99%
“…However, a recent publication with 122 patients found that an area with MR restricted diffusion over 1 cm was seen after 22% of meningioma operations and was associated with postoperative deficits [ 16 ]. A recent study found that postoperative ischemia, defined as ischemia/infarction found on postoperative MRI not related to normal postoperative changes within the resection bed, occurred in 13 of 57 (23%) cases and was associated with postoperative seizures [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…MIB-1 index is an almost unknown variable among the determinants of symptomatic epilepsy in meningioma patients. Only one recent retrospective series investigating 384 meningioma patients revealed that an elevated MIB-1 index is an independent predictor of postsurgical seizure persistence [ 68 ]. Seizure is known to have a negative impact on health-related quality of life in meningioma patients [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…More recently, the genetic drivers of epileptogenicity in meningiomas have been investigated. NF2 mutation was shown to be predictive marker for preoperative seizures, which was via an indirect mediation effect with atypical histology and edema ( 25 ). Meningioma originates from arachnoid cap cells and is usually a slow-growing tumor ( 1 ).…”
Section: Pathogenesis Of Epilepsy In Meningiomamentioning
confidence: 99%
“…However, there was an associative tendency between subtypes of higher grades (malignant, rhabdoid) with worse postoperative seizure outcomes. The subtypes of lower grades (fibrous, transitional) trended toward improved postoperative outcomes (p = 0.081) ( 25 ). There are no data in the medical literature for the incidental small meningioma, which are not part of the epileptogenic network.…”
Section: Pathogenesis Of Epilepsy In Meningiomamentioning
confidence: 99%